Numerical study of micromixing combining alternate flow and obstacles - Miranda, J. M. (2010)
Mixing in microsystems, combining alternate flow with obstacles, is studied by numerical methods. Simulations show that the layers of high and low solute concentrations, created by the alternate flow, are split into smaller chunks of fluid by obstacles inserted in the mixing channel, decreasing the critical mixing length. Reverse flow is necessary to guarantee symmetry and good mixing. Mixing increases with the increase of the number of obstacles. Increase of frequency improves mixing but requires an increase of reverse flow. The improvement in the mixing process shows that this method is very useful for designing mixers for lab-on-a-chip devices.